2020
DOI: 10.1186/s13059-020-02042-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 1321 Eubacterium rectale genomes from metagenomes uncovers complex phylogeographic population structure and subspecies functional adaptations

Abstract: Background: Eubacterium rectale is one of the most prevalent human gut bacteria, but its diversity and population genetics are not well understood because large-scale whole-genome investigations of this microbe have not been carried out. Results: Here, we leverage metagenomic assembly followed by a reference-based binning strategy to screen over 6500 gut metagenomes spanning geography and lifestyle and reconstruct over 1300 E. rectale high-quality genomes from metagenomes. We extend previous results of biogeog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 84 publications
(134 reference statements)
9
68
1
Order By: Relevance
“…Strains abundant in the infant gut are only rarely abundant in maternal microbiomes [31][32][33][34] and are often replaced within the first 1-2 years of life [35,45], but even small structural variants may be crucial in immune programming during temporally specific developmental windows [38][39][40][41]. Ultimately, microbial strain variants affect not only host and individual microbes' physiology, but also the ecology and phylogenetics of the overall gut community: Helicobacter pylori is one of the best-known examples of resident microbial genetic variation paralleling that of human host populations [46], but this has recently been shown to be the case for multiple subsets of the gut microbiome, such as Prevotella copri [12] or Eubacterium rectale [47]. This leads to linkages between the evolution and diversification of gut microbial community strains and host migration, geography, and lifestyle [8,48].…”
Section: Strains In the Human Gut Microbiomementioning
confidence: 99%
“…Strains abundant in the infant gut are only rarely abundant in maternal microbiomes [31][32][33][34] and are often replaced within the first 1-2 years of life [35,45], but even small structural variants may be crucial in immune programming during temporally specific developmental windows [38][39][40][41]. Ultimately, microbial strain variants affect not only host and individual microbes' physiology, but also the ecology and phylogenetics of the overall gut community: Helicobacter pylori is one of the best-known examples of resident microbial genetic variation paralleling that of human host populations [46], but this has recently been shown to be the case for multiple subsets of the gut microbiome, such as Prevotella copri [12] or Eubacterium rectale [47]. This leads to linkages between the evolution and diversification of gut microbial community strains and host migration, geography, and lifestyle [8,48].…”
Section: Strains In the Human Gut Microbiomementioning
confidence: 99%
“…14,15 Indeed, extensive human gut metagenome studies have reported the recovery of a large complement of metagenome-assembled Eubacterium rectale genomes irrespective of geographical location, age, lifestyle and clinical status. 16,17 Interestingly, while Eubacterium spp. are routinely recovered from animal gut, an absence of E. rectale have been reported in primate gut; coupled with its omnipresence in the human gut this suggests a high degree of specificity and adaptation for the latter.…”
Section: Introductionmentioning
confidence: 99%
“…are routinely recovered from animal gut, an absence of E. rectale have been reported in primate gut; coupled with its omnipresence in the human gut this suggests a high degree of specificity and adaptation for the latter. 17 Multiple species of the genus are currently regarded as promising targets for microbial therapeutics. Indeed, recent consensus among gut microbiologists suggests that specific strains of butyrate-producing microbes belonging to the genera Eubacterium, Roseburia and Faecalibacterium, among others, may ultimately be considered as beneficial to human health in the same manner as strains of Lactobacillus and Bifidobacterium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have applied functional enrichment or depletion analyses to a pangenome to investigate adaptation to the particular habitats from which those genomes were obtained (Cornejo et al, 2013;Martino et al, 2016;Simon et al, 2017). Genomic biogeographic patterns also exist at the global scale, as shown by a recent study that identified differentiation in the motility and metabolic potential of European E. rectale populations relative to those from other continents (Karcher et al, 2020). Another recent study used methods conceptually similar to ours, i.e., using metagenomic abundances of reference genes to detect ecologically different subgroups within a population, to identify genes important for determining which Bacteroides strains engrafted from human mothers to infants (Yassour et al, 2018).…”
Section: Niche Adaptation At the Genomic Levelmentioning
confidence: 99%